2022
DOI: 10.21203/rs.3.rs-2040502/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolomic analysis on the mechanism of nanoselenium alleviating cadmium stress and improving the chili pepper nutritional value

Abstract: Selenium (Se) can maintain rhizosphere soil-plant homeostasis and regulate signaling molecules to mitigate cadmium (Cd) toxicity. However, no systematic studies on the intervention of nano-selenium (nano-Se) in regulating non-target metabolites and fruit nutritional components in pepper plants under Cd stress were investigated. This study researched the effects of Cd-contaminated soil stress and nano-Se (1, 5, and 20mg/L) on the metabolic mechanism, fruit nutritional quality, and volatile organic compounds (VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Additionally, Nano-Se can increase pepper's resistance to cadmium stress and lessen the harm caused by cadmium stress. 193 Kang 21 et al found that the mesophyll cells of melon leaves had fewer plastids, a maintained thylakoid membrane, more starch granules, and thickened cell walls in their examination of the effects of applying Nano-Se to several melon varieties. The Nano-Se treatment increased cucurbitacin B related synthesis gene expression as well as the antioxidant activity of the enzymes ascorbate peroxidase, peroxidase, phenylalanine ammonialyase, −1,3-glucanase, and Chitinase.…”
Section: Cucumber Rootsmentioning
confidence: 99%
“…Additionally, Nano-Se can increase pepper's resistance to cadmium stress and lessen the harm caused by cadmium stress. 193 Kang 21 et al found that the mesophyll cells of melon leaves had fewer plastids, a maintained thylakoid membrane, more starch granules, and thickened cell walls in their examination of the effects of applying Nano-Se to several melon varieties. The Nano-Se treatment increased cucurbitacin B related synthesis gene expression as well as the antioxidant activity of the enzymes ascorbate peroxidase, peroxidase, phenylalanine ammonialyase, −1,3-glucanase, and Chitinase.…”
Section: Cucumber Rootsmentioning
confidence: 99%